Scientific Progress of Medicine and Pharmacy of the Eu Countries 2021
DOI: 10.30525/978-9934-26-075-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the characteristics of the gallbladder in patients with chronic cholecystitis and COPD

Abstract: 2. The relationship between pelvic vein incompetence and chronic pelvic pain in women: systematic reviews of diagnosis and treatment effectiveness / R. Champaneria et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A clinical trial of 666 subjects (256 patients with liver diseases and 410 patients without liver diseases) showed that the prevalence of COPD was higher in patients with liver diseases (28). Furthermore, the prevalence of aseptic inflammation of the gallbladder is associated with COPD exacerbations (29).…”
Section: Gastrointestinal Tract Disorders Associated With Copdmentioning
confidence: 99%
“…A clinical trial of 666 subjects (256 patients with liver diseases and 410 patients without liver diseases) showed that the prevalence of COPD was higher in patients with liver diseases (28). Furthermore, the prevalence of aseptic inflammation of the gallbladder is associated with COPD exacerbations (29).…”
Section: Gastrointestinal Tract Disorders Associated With Copdmentioning
confidence: 99%